Pendidikan Karakter Islam Siswa Sekolah Dasar Perspektif Filsafat Idealime - Syahriani, Nur (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The formation of student character at the elementary school level is an important foundation for developing quality personalities. This research focuses on the philosophical study of Islamic character education using an idealistic perspective, which aims to reveal the nature of fostering noble morals based on Islamic values. Through library research methods, the research uses a philosophical idealism approach to analyze the construction of character development which prioritizes spiritual and intellectual dimensions. Content analysis and critical interpretation methods are applied to explore ideal concepts in Islamic character education. The study focused on the mechanism of internalization of spiritual values in forming holistic and characterful elementary school students' personalities. Research findings reveal that the concept of Islamic character education from an idealistic perspective offers a transformative paradigm that integrates spiritual, intellectual and moral dimensions. This philosophical approach emphasizes the importance of building inner awareness, developing intellectual potential, and cultivating universal and meaningful morals. The contribution of this research lies in the in-depth philosophical meaning of Islamic character education, providing a conceptual framework that can be used as a reference for educational practitioners in designing sustainable and comprehensive character development strategies for elementary school students.